Effects of AB Mix hydroponic solution and ameliorant mixtures on cayenne pepper growth and yield in an Inceptisols - Turmuktini, Tien; Fitriatin, Betty Natalie; Simarmata, Tualar; Widayanti, Firda; Nuryanti, Nuryanti; Amalia, Lia; Ria, Elly Roosma; Parlinah, Linlin (Universitas Padjadjaran, 2026)
Cayenne pepper (Capsicum frustescens L.) cultivation faces several problems, including acidic pH and inadequate nutrient management. These problems can be addressed by using a mixture of various ameliorants and AB mix nutrient solutions. This study aimed to determine the effect of ameliorant mixture dosage and AB mix solution concentration on soil chemical properties, growth, and yield of cayenne pepper. The experiment used a randomized block design, consisting of two factors: nutrient solution concentration and ameliorant dosage. The factor of nutrient solution concentration consisted of four levels, i.e., 700, 1000, 1300, and 1600 ppm, while the factor of ameliorant dosage also consisted of four levels, i.e., 0, 2, 4, and 6 t ha-1. Observations were made on soil chemical properties, namely soil pH, organic carbon content, and cation exchange capacity (CEC). The agronomic characteristics observed were plant height, number of leaves, leaf area, chlorophyll content index, fruit length, number of fruits, and fruit weight per plant. The results showed no interaction between the concentration of AB mix solution and the ameliorant dosage on soil chemical properties, growth, and yield characteristics of cayenne pepper plants. The single effect of AB mix solution or ameliorant was observed on the number and weight of fruits per plant. The optimal dose for achieving the maximum harvested fruit weight was 6 t ha-1 of the ameliorant mixture (76.55 g pepper/plant), while the optimal AB mix concentration was 1600 ppm (65.02 g pepper/plant).